2012
DOI: 10.1590/s1678-77572012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of systemic antibiotics used in periodontal treatment and mechanisms of bacterial resistance to these drugs

Abstract: Antibiotics are important adjuncts in the treatment of infectious diseases, including periodontitis. The most severe criticisms to the indiscriminate use of these drugs are their side effects and, especially, the development of bacterial resistance. The knowledge of the biological mechanisms involved with the antibiotic usage would help the medical and dental communities to overcome these two problems. Therefore, the aim of this manuscript was to review the mechanisms of action of the antibiotics most commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(102 citation statements)
references
References 167 publications
3
91
1
7
Order By: Relevance
“…As little is known about mechanisms of antibiotic resistance in A. actinomycetemcomitans, we next decided to use the ordered library to screen for genes involved in erythromycin resistance. Macrolides, such as erythromycin, inhibit formation of the 50S ribosomal subunit (26) and represent one of the most commonly used classes of antibiotics for treating periodontal disease (24). To perform this screen, we first determined that the MIC of erythromycin for A. actinomycetemcomitans is 2 g/ml, which falls within previously reported ranges (27).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As little is known about mechanisms of antibiotic resistance in A. actinomycetemcomitans, we next decided to use the ordered library to screen for genes involved in erythromycin resistance. Macrolides, such as erythromycin, inhibit formation of the 50S ribosomal subunit (26) and represent one of the most commonly used classes of antibiotics for treating periodontal disease (24). To perform this screen, we first determined that the MIC of erythromycin for A. actinomycetemcomitans is 2 g/ml, which falls within previously reported ranges (27).…”
Section: Resultsmentioning
confidence: 90%
“…Though periodontitis is treatable by eliminating plaque physically, many cases of periodontitis are highly refractory and necessitate chemical treatment with antibiotics (22,23). However, antibiotic resistance among periodontal pathogens is widespread (24), motivating a search for alternative therapies and a better understanding of bacterial resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, isolates of A. baumannii usually present multidrug resistance, including resistance to third generation cephalosporins, aminoglycosides, and fluoroquinolone (Sinha and Srinivasa, 2007). Previous experimental study has reported that the most common mechanism of drug resistance is the presence of hydrolyzing β-lactamases, including metallo-β-lactamases (Ambler class B) and oxacillinases (Ambler class D) (Soares et al, 2012). The widespread use of antimicrobial chemotherapy has played an important role in the appearance of carbapenem-hydrolyzing class D β-lactamases (CHDLs), which have been widely identified in A. baumannii.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of pharmaceutical antibiotics is associated with a raise in resistant bacterial strains, although this aspect has been poorly studied in dentistry (Soares et al, 2012). Natural phytochemicals may be effective in overcoming this problem as well as minimizing adverse effects of some antibiotics (Palombo, 2011).…”
Section: Introductionmentioning
confidence: 99%